2020
DOI: 10.1128/msphere.00852-20
|View full text |Cite
|
Sign up to set email alerts
|

Dolosigranulum pigrum Cooperation and Competition in Human Nasal Microbiota

Abstract: Multiple epidemiological studies identify Dolosigranulum pigrum as a candidate beneficial bacterium based on its positive association with health, including negative associations with nasal/nasopharyngeal colonization by the pathogenic species Staphylococcus aureus and Streptococcus pneumoniae. Using a multipronged approach to gain new insights into D. pigrum function, we observed phenotypic interactions and predictions of genomic capacity that support the idea of a role for microbe-microbe interactions involv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
97
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(127 citation statements)
references
References 106 publications
17
97
1
1
Order By: Relevance
“…However, determining whether this was due to outcompeting the neighboring strain for nutrients, or if there was another metabolic interaction between the strains, was not an objective of our BaQFA experiments. It could still be hypothesized that with our BaQFA method, bacterial interactions might be quantified, as they have been described similarly in vivo and in vitro ( 8 , 9 ). Although we regard the results from our method validation work to only be of an exploratory nature, we could observe a substantially increased fitness in the methicillin-resistant JE2 strain compared to the methicillin-susceptible Cowan strain, suggesting a different baseline-fitness of the underlying USA300 background in JE2 compared to Cowan or the presence of compensatory mutations or other mechanisms of fitness gain.…”
Section: Discussionmentioning
confidence: 92%
“…However, determining whether this was due to outcompeting the neighboring strain for nutrients, or if there was another metabolic interaction between the strains, was not an objective of our BaQFA experiments. It could still be hypothesized that with our BaQFA method, bacterial interactions might be quantified, as they have been described similarly in vivo and in vitro ( 8 , 9 ). Although we regard the results from our method validation work to only be of an exploratory nature, we could observe a substantially increased fitness in the methicillin-resistant JE2 strain compared to the methicillin-susceptible Cowan strain, suggesting a different baseline-fitness of the underlying USA300 background in JE2 compared to Cowan or the presence of compensatory mutations or other mechanisms of fitness gain.…”
Section: Discussionmentioning
confidence: 92%
“…In this step, the model-predicted phenotypes are compared with the experimental data [ 60 ]. Brugger et al predicted the biosynthesis, uptake, and degradation of amino acids, carbohydrates, polyamines, and enzyme cofactors in eleven D. pigrum strains by evaluating their genetic content [ 25 ]. COBRApy [ 61 ] was used for all evaluation steps.…”
Section: Resultsmentioning
confidence: 99%
“…We identified and removed four reactions without evidence in KEGG [ 37 ], BioCyc [ 51 ], or a significant hit in a BLAST search [ 62 ]. With these alterations, the model is now incapable of producing methionine, as Brugger et al observed in their study [ 25 ]. An ATP-binding cassette (ABC) transporter for the uptake of methionine is present in the model.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations